Empirical tests of the homology assumption in criminal profiling - Doan, Brandy, 1972- (2009)
Thesis (M.Sc.)--Memorial University of Newfoundland, 2009. Psychology Includes bibliographical references (leaves 41-47) A fundamental assumption in criminal profiling, known as the homology assumption, is that criminals who exhibit similar crime scene actions have similar background characteristics. The homology assumption was tested by first classifying, with a pre-existing typology, a sample of arsonists (N = 87) and robbers (N = 111) into different crime types and then comparing the similarity of their background characteristics. Study 1 tested the homology assumption with Canter and Fritzon's (1998) arson typology, and for Study 2, Alison, Rockett, Deprez and Watts' (2000) robbery typology was used. Results showed that using pre-existing typologies to classify crimes into mutually exclusive types was not easily accomplished. Notwithstanding classification difficulties, the homology assumption was violated in 56% of the comparisons between the different types of arsonists and in 67% of the comparisons between the different types of robbers. Overall, these two studies failed to provide empirical support for the homology assumption for typology-based profiling practices. These findings indicate that using established typologies to profile offenders might not be very useful. Future research endeavors that wish to examine the validity of the homology assumption should first seek reliability with typologies across several geographic regions.